Challenges and opportunities confronting female-headed households in Iran: a qualitative study - Javad Yoosefi Lebni; Mohammad Ali Mohammadi Gharehghani; Goli Soofizad; Bahar khosravi; Arash ziapour; Seyed Fahim Irandoost (BMC, 2020)
Abstract Background Female-headed households are one of the most vulnerable groups of society that confront many problems and challenges. Therefore, the present study aimed to explore the challenges and opportunities confronting female-headed households in Iran. Methods This qualitative study was conducted among female-headed households in Kermanshah, West of Iran, in 2019. The data were collected through Semi-structured interviews with 26 female-headed households who were selected by purposeful and theoretical sampling. Data analysis was done through conventional qualitative content analysis, and the software MAXQDA-12 was used for the management of data. The four criteria of Goba and Lincon, including credibility, confirmability, dependability, and transferability, were observed to evaluate the quality of research results. Results After analyzing the data, 4 main categories and 13 subcategories were obtained as follows: individual problems (role overload, role conflict, end of love, psychological problems), intra-family problems (declined independence, intra-family tension, poverty reproduction and family disability), social problems (stigma of being unattended, social insecurity, social isolation, social exclusion), positive outcomes (positive self-concept, social maturity). Conclusion Female-headed households face many challenges that can become a big threat or an opportunity. Therefore, their health improvement can be achieved through training and helping them to adapt to new and multifaceted roles, providing more economic support and helping them raise their social status.